Sustainability using cover crops in Mediterranean tree crops, olives and vines – Challenges and current knowledge - Gómez, José A (Hungarian Geographical Bulletin, 2017)
Tree crops cover a large area of European landscape, 13.3 million hectares, with olive, grapes, nuts and almonds been the most extended and mostly concentrated in Mediterranean areas. The cultivation of tree crops in rain limited Mediterranean areas depend on an adequate management of water balance that, been historically mostly based on bare soil, has created severe erosion and offsite contamination problems. Temporary cover crops can be an alternative to control these problems with a larger effect on erosion control than on reducing runoff, and a moderate impact on soil properties. This impact depend strongly on the ability to implement temporary cover crops that achieve a significant development during the rainy season while simultaneously minimizing the competition for soil water with the major crop, which is not always easy in commercial farms. This balance between soil protection and yield has been achieved in some conditions but not in others, and a significant reduction in yield has been reported for some situations. This potential risk of yield decrease, combine with the difficulty to see a collapse in yield due to soil degradation by water erosion in the short/medium term can explain, partially, the reluctance of farmers for an extensive use of temporary cover crops. The development of improved strategies for using temporary cover crops which could include the use of water balance models, new varieties better adapted to the region, and strategies for restoring ground cover in severely degraded orchards seems to be necessary, coupled with regulations and incentive to their use by farmers. Future research should focus in the less understood elements of this system, among them root development, biomass production, phenology under different microclimate of the cover crops and the main tree crops, use of cover crops mixes, which are hampering the tuning of the system for specific conditions. It is also necessary a better definition and measurement of the impacts of cover crops on biodiversity that should be related to the landscape conditions.